Global Perspectives on Obesity and the Burden of Health Risks on Women: The Perspectives of Health Workers in Ghana - Amuzu, P. S. (University of Ghana, 2024)
Obesity has emerged as a critical global health challenge, increasingly affecting populations in low- and middle-income countries, including Ghana. This qualitative study explores the perspectives of health workers in Ghana on the rising burden of obesity and its associated health risks for women. Drawing on the Constructivist theoretical framework, the study investigates three key areas: the capacity of health workers to accurately diagnose and manage obesity among women; the socio-cultural, economic, and environmental determinants of obesity; and the systemic challenges Ghana faces in addressing obesity-related health concerns. Data were collected through semi-structured interviews with sixteen healthcare professionals across diverse public and private institutions in urban Ghana. Thematic analysis revealed eight major themes, including diagnostic limitations due to overreliance on BMI, inadequate interdisciplinary training, cultural norms valorizing larger body sizes, economic barriers to care, and environmental factors such as urbanization and limited recreational infrastructure. The findings also highlighted systemic constraints such as the lack of national obesity guidelines, fragmented care pathways, and limited follow-up mechanisms. Despite these challenges, participants identified opportunities for intervention through culturally sensitive education, improved insurance coverage, and community based prevention programs. The study concludes that obesity among women in Ghana is shaped by a confluence of clinical, socio-cultural, economic, and structural factors, and recommends integrated, context-specific, and gender-responsive policy responses. This research contributes to the global discourse on obesity by centering the voices of frontline healthcare providers and offering practical insights for enhancing women’s health equity in Ghana.
MA. International Affairs
Keywords: Obesity; health; low- and middle-income countries